2022
DOI: 10.1111/imig.13011
|View full text |Cite
|
Sign up to set email alerts
|

Free versus regulated migration: Comparing the wages of the New Zealand‐born, other migrants and the Australia‐born workers in Australia

Abstract: New Zealanders can cross borders freely, work and live in Australia indefinitely thanks to the Trans‐Tasman Travel Agreement. This paper uses a recently developed decomposition method to decompose the weekly wage gap at various quantiles on the wage distribution between New Zealand‐born (NZ‐born) and Australian‐born workers, and between NZ‐born workers, migrants from other English speaking countries (OESC), and from non‐English speaking countries (NESC) to determine how free and regulated migration influences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“… Kifle & Desta, 2012 ; Taouk, Milner, & LaMontagne, 2019 ; Keramat et al, 2021 ). For example, Australia has a very high proportion of immigrants (about 30% born overseas) and also has a very large geographic coverage spanning over six states and two territories, with diverse labour market patterns in terms of wage income and workhours across location and ethnicity ( Doan et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“… Kifle & Desta, 2012 ; Taouk, Milner, & LaMontagne, 2019 ; Keramat et al, 2021 ). For example, Australia has a very high proportion of immigrants (about 30% born overseas) and also has a very large geographic coverage spanning over six states and two territories, with diverse labour market patterns in terms of wage income and workhours across location and ethnicity ( Doan et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent advances in econometric techniques allow one to decompose the drivers of differences by ethnicity, such as wage gaps or household expenditure gaps in this context, into composition effects (gaps due to individual and household characteristics) and structure effects (gaps due to returns to individual and household characteristics) ( Firpo et al, 2009 , 2018 ). Doan et al (2022) showed that differences in worker and job characteristics were primarily responsible for the wage gaps between NZ-born and Australian-born workers, and between NZ-born and other English speaking migrants, but differences in returns to worker and job characteristics are mainly responsible for the wage gap between NZ-born and non-English speaking background (NES) migrants in Australia. Barriers to NES migrants remain in the Australian labour market, where there is still significant unequal treatment to NES migrants.…”
Section: Introductionmentioning
confidence: 99%